Formal Validation of DNA Database Using Theorem Proving Technique - Julaily Aida, Jusoh (2010)
This paper discusses the formal validation of DNA database system. A DNA database is a large, organized body of persistent data, usually associated with computerized software designed to update, query, and retrieve components of the data stored within the system. One of the common difficulties faced by the developer is in designing a robust database system. Even so, in order to solve this matter, developers have to focus their efforts on the formal specifications. This is supposed to reduce the overall development time. Formal specifications can be use to provide an unambiguous and precise supplement to natural language descriptions. Besides, it can be rigorously validate, and verified leading to the early detection of specification errors. Consequently, to validate this problem formally, we specify the DNA database system using Z language and prove by using Z/EVES theorem prover tool. By using this kind of tools, it may helps to reduce time, energy and mistake compared to manual theorem proving which can be error task and tedious